Influences of molecular weight fractionated humic acids on polyamide 66 microplastic stability and toxicity in red tilapia (Oreochromis niloticus) - Zheng, Lixing; Ding, Jiannan; Xu, Hui; Tian, Wenqing; Xu, Jianyun; Zou, Hua; Zhu, Wenbin (Frontiers in Marine Science, 2022)
Dissolved organic matter (DOM) is likely to coexist with microplastics (MPs) in aquatic environments. However, little is known about the effects of different DOM fractions on the stability and aquatic toxicity of MPs. In this study, we separated humic acid (HA) into three molecular weight (MW) fractions (> 30, 3–30, and < 3 k Da) and examined their effects on the toxicity of polyamide 66 (PA66)-MPs to red tilapia (Oreochromis niloticus). Generally, addition of HA enhanced the stability and thus the exposure of tilapia to MPs, leading to the increased accumulation of MPs in the gut, liver, and brain. However, compared with MPs alone, the accumulation of MPs in the gills of tilapia was reduced. Compared with the presence of high-MW HA, the accumulation of MPs in the fish liver was significantly enhanced by 1.1 times in the presence of medium-MW HA (m-HA) after a 10-day exposure. The protein peroxidation on the liver induced by MPs was alleviated by adding all HA fractions. However, compared with MPs alone, the presence of m-HA resulted in a more severe lipid peroxidation, while the presence of low-MW HA alleviate the lipid peroxidation caused by MPs. In addition, the Integrated Biological Responses version 2 (IBRv2) results suggested that the oxidative stress in the liver tilapia caused by MPs could be alleviated by the presence of all HA fractions, which was largely related to the reduced damage caused by lipid peroxidation and/or protein peroxidation. Collectively, our results suggest that the presence of different MW HA fractions could induce complex changes in the MP toxicity on aquatic organisms.